Administrative Law and the Efficiency of Local Government Budgeting - Fitria, Fitria; Nuriyatman, Eko; Amir, Latifah; Sitta Saraya (As-Siyasi: Journal of Constitutional Law, 2025)
This article examines applying the general principles of good governance within the framework of administrative law as a strategy to promote more efficient and accountable regional budget management in the era of fiscal decentralization. This research aims to analyze how the General principles of good governance, as codified in Indonesian administrative legislation, can serve as a legal foundation to overcome normative and administrative barriers in realizing budget efficiency at the regional level. Using a normative legal research method through statutory and conceptual approaches, this article identifies key legal and institutional challenges, including overlapping regulations, weak bureaucratic capacity, and limited digital infrastructure. The study emphasises the implications of Presidential Instruction No. 1 of 2025 on the Efficiency of State and Regional Budget Expenditure, which mandates stricter fiscal discipline and performance-oriented budget allocation. The analysis focuses on several key regulations, including Law No. 30 of 2014 on Government Administration, Law No. 23 of 2014 on Regional Government, Law No. 1 of 2022 on Central Regional Fiscal Relations, and Government Regulation No. 12 of 2019 on Regional Financial Management. It also includes an examination of the role of digital systems, such as the regional government information system and the regional financial accounting information system. The findings affirm that the consistent implementation of the general principles of good governance, particularly transparency, accountability, legal certainty, and proportionality, when supported by regulatory harmonization, technological innovation, and inclusive public oversight, can significantly improve the effectiveness of regional financial governance and foster a democratic, accountable, and sustainable government administration